The Dynamics of the Implementation of Islamic Law in Aceh: Historical Challenges and Issues - Muchsin, Misri A.; Armi, Fadhlur Rahman (Hikmah, 2024)
Aceh is known as a region that is characterized by the application of Islamic law in its life system. However, the implementation does not always go well, there are challenges and problems faced. In this regard, this research aims to analyze the implementation of Islamic sharia in Aceh during the sultanate era and how the implementation of Islamic sharia during Aceh's time as a province of the Republic of Indonesia. The study uses a descriptive historical approach and method, so that data verification of the application of Islamic sharia periodically can be collected, analyzed and explained easily periodically. The results show that Islamic Shari'a in Aceh has been enforced since the sultanate era. For example, during the time of Sultan Alaiddin Ri'ayat Syah II al-Qahhar who applied qishash law against his son. Similarly, Sultan Iskandar Muda sentenced his son, Meurah Pupok, to stoning after he was found guilty of adultery. During Aceh's time as one of the provinces of Indonesia, the implementation of Islamic sharia refers to the laws of Aceh's specialty and regional autonomy, namely Law No. 1/1957, Law No. 44/1999; Qanun No. 5/2000, Law No. 11/2006; Qanun No. 2/2009; MPU Fatwa No. 11/2013, and Qanun No. 8/2014.